2020
DOI: 10.1187/cbe.19-11-0255
|View full text |Cite
|
Sign up to set email alerts
|

Modeling in the Classroom: Making Relationships and Systems Visible

Abstract: As an instructional tool, models can transform the student experience from the static to the dynamic, the flat to the 3D, and the siloed to the integrated. Few practical resources exist to help instructors transition toward model-based classroom practices. The Modeling in the Classroom evidence-based teaching guide provides instructors with a tool kit for incorporating models and modeling into their classrooms ( https://lse.ascb.org/evidence-based-teaching-guides/modeling-in-the-classroom ). The guide discusse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 10 publications
2
20
0
1
Order By: Relevance
“…Studies have shown that modelling is particularly suited for small-group work, as it permits students to communicate more during the modelling process. 10,19 As in our study, using a small group in MBI enhances the discussion among the group when selecting the components that are required to demonstrate the model. Such interactions not only facilitate the selection of the representation mode but also increase the likelihood that students will understand the knowledge through self and peer learning.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Studies have shown that modelling is particularly suited for small-group work, as it permits students to communicate more during the modelling process. 10,19 As in our study, using a small group in MBI enhances the discussion among the group when selecting the components that are required to demonstrate the model. Such interactions not only facilitate the selection of the representation mode but also increase the likelihood that students will understand the knowledge through self and peer learning.…”
Section: Discussionmentioning
confidence: 84%
“…This approach provides instructors with insight into student thinking and allows students to improve their knowledge through different modes. 28,29 The models that are created by students can enhance the students' critical thinking and promote deep and long-lasting learning by engaging them in the learning process. 28 This is an important consideration since some pharmaceutics courses are generally taught in the early stages of number of PharmD programme curriculum and may gradually be forgotten by the time student's graduate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…, 2015 ). According to Wilson et al. (2020 , p. 5), models can change students’ views on biological processes “from the static into the dynamic, the flat to the 3D, and siloed to integrated.” Two types of models are computational and qualitative.…”
Section: Recommendations From the Literaturementioning
confidence: 99%
“…Literature shows that, when done properly, virtual educational experiences can be as effective as traditional teaching, even in lab-based courses. Furthermore, virtual education may be improved by using modeling and simulations (1)(2)(3)(4). In 2011, the American Association for the Advancement of Science Vision and Change document established educational foci to include using models and simulations (competency #3) and understanding complex systems (core concept #5) (5).…”
Section: Introductionmentioning
confidence: 99%